The radical element : 12 stories of daredevils, debutantes, and other dauntless girls - Spotswood, Jessica (Candlewick Press, 2018)
An anthology of historical short stories features a diverse array of girls standing up for themselves and their beliefs, forging their own paths while resisting society's expectations.